Serving Web Content with Dynamic Process Networks in Go - Ii, W; James (2011)
This paper introduces webpipes, a compositional web server toolkit written using the Go programming language as part of an investigation of concurrent software architectures. This toolkit utilizes an architecture where multiple functional components respond to requests, rather than the traditional monolithic web server model. We provide a classification of web server components and a set of type definitions based on these insights that make it easier for